2017
DOI: 10.1016/j.cemconcomp.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic orientation of steel fibres in self-compacting concrete beams: Effect on failure behaviour

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Several studies found an increase of resistance up to 20% for inclination angles of up to 60° (Van Gysel 2000;Robins, Austin, and Jones 2002), whereas another work found an important decrease of resistance leading up to 50% at 60° (Bartos and Duris 1994). Yet, others noted that the post-fracture resistance and energy absorption significantly reduces for inclination angles over 30° (Banthia and Trottier 1994;Armelin and Banthia 1997;Svec et al 2012), supported by a study on the effect of the magnetic orientation of fibers (Wijffels et al 2017). When corrected for a fixed limited value of fiber slip, several studies indicate an optimal pull-out resistance is reached at inclination angles of 10-15° (Markovic 2006).…”
Section: Structural Performance Of Concrete Reinforced With Straight Steel Fibersmentioning
confidence: 96%
“…Several studies found an increase of resistance up to 20% for inclination angles of up to 60° (Van Gysel 2000;Robins, Austin, and Jones 2002), whereas another work found an important decrease of resistance leading up to 50% at 60° (Bartos and Duris 1994). Yet, others noted that the post-fracture resistance and energy absorption significantly reduces for inclination angles over 30° (Banthia and Trottier 1994;Armelin and Banthia 1997;Svec et al 2012), supported by a study on the effect of the magnetic orientation of fibers (Wijffels et al 2017). When corrected for a fixed limited value of fiber slip, several studies indicate an optimal pull-out resistance is reached at inclination angles of 10-15° (Markovic 2006).…”
Section: Structural Performance Of Concrete Reinforced With Straight Steel Fibersmentioning
confidence: 96%
“…In case the concrete printing material is reinforced by fibres, the microstructural stiffening effect by the fibres should be accounted for in the calibration of Eq. 4, although the influence may be negligible for low fibre volume percentages [32].…”
Section: Elastic Bucklingmentioning
confidence: 99%
“…The orientation of the fibres can affect the impact resistance of the composite [ 83 , 84 , 85 ]. All FTSFC specimens had a planar orientation of fibres in the majority of cases.…”
Section: Discussion Of Resultsmentioning
confidence: 99%